2017
DOI: 10.1515/jmmm-2016-0154
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically nonlinear large deformation of CNT-reinforced composite plates with internal column supports

Abstract: Abstract:The geometrical nonlinear analysis of internally supported nanocomposite plates subjected to a uniformly distributed load is carried out. This study investigates the effects of internal point/column supports on the large deformation bending of nanocomposite plates reinforced by carbon nanotubes (CNTs) with different types of distributions, namely, uniform and two kinds of functionally graded distributions through the thickness of the plates. Two-dimensional displacement field of the plate is approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…They observed that the gradient material properties play a vital role in the response of the FGM plates. Zhang [ 4 ] carried out a geometric non-linear analysis of CNT-reinforced FGM plates with column support. For modeling the structure, they used FSDT mathematical model with the von Kármán nonlinearity equation.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the gradient material properties play a vital role in the response of the FGM plates. Zhang [ 4 ] carried out a geometric non-linear analysis of CNT-reinforced FGM plates with column support. For modeling the structure, they used FSDT mathematical model with the von Kármán nonlinearity equation.…”
Section: Introductionmentioning
confidence: 99%
“…Shen 11 first employed the idea of FGMs in the distribution of CNTs within the isotropic matrix to utilize the low content CNTs optimally and proposed functionally graded CNTs reinforced composites (FG-CNTRCs). Afterward, Zhang et al carried out extensive research works on linear and nonlinear bending, [12][13][14][15][16] buckling, 17 postbuckling, 18,19 free vibration, [20][21][22] dynamic, 23 elastodynamic, 24 and aerothermoelastic 25 behavior of FG-CNTRC plates using various structural theories and solution methods. To reveal more about the mechanical behaviors of FG-CNTRC plates/shells, the review articles reported by Liew et al 26,27 are recommended.…”
Section: Introductionmentioning
confidence: 99%